Navigating complex realities: Barriers to health care access for undocumented African immigrant women in the United States. Issue 2 (1st February 2021) - Olukotun, Oluwatoyin; Mkandawire-Valhmu, Lucy; Kako, Peninnah
Abstract: Undocumented immigrants encounter a myriad of complex barriers to health care access, negatively impacting their health outcomes. In this qualitative study we aimed to understand the barriers to health care for undocumented African immigrant women in the United States as well as how women navigate these barriers. Semi-structured interviews were conducted with 24 undocumented African immigrant women. Our findings indicate that undocumented African women experience complex barriers to care which they attempted to navigate. In this study we provide information that healthcare professionals can employ in attending to the health needs of undocumented women and creating safe spaces for them to seek care.